104 COVID-19 Exposure and Care-Seeking Behaviors Among Vulnerable Urban Adolescents and Young Adults–Baltimore, Maryland USA. (April 2022) - Nickelberry, Marshae; Matson, Pamela A.; Agwu, Allison; Van Eck, Kathryn; Perin, Jamie; Coleman, Jenell; Trent, Maria
Abstract : OBJECTIVES/GOALS: This study seeks to determine the relationship between fear of COVID-19 infection and care-seeking behaviors including provider visit and telemedicine utilization among vulnerable adolescent and young adults in Baltimore, Maryland METHODS/STUDY POPULATION: Participants enrolled in the COVID-19 Youth study were 13-25 years old and recruited from four existing sexual health studies based in Baltimore, MD which focused on 1) PID, 2) HIV, 3) emerging sexually transmitted infections, and 4) a dyadic STI prevention, respectively. Participants agreed to be re-contacted for future studies and completed a telephone survey developed to inquire about the impacts of COVID-19 on care seeking behaviors. Bivariate analyses tested for correlations between fear of COVID-19 infection, demographic variables, and care-seeking behaviors. Multivariable logistic regression modeled associations between fear of COVID-19 infection and care-seeking behaviors. RESULTS/ANTICIPATED RESULTS: Adjusted multivariable logistic regression revealed a statistically significant association between fear of COVID-19 infection and having a provider visit; AYA who feared COVID-19 were at greater than two times increased odds of a provider visit compared to AYA who did not fear COVID-19 infection (OR: 2.37, 95%CI: 1.02, 6.15). Among those with a provider visit, fear of COVID-19 infection was associated with two-fold increased odds of having a telemedicine visit vs. an in-person visit (OR: 2.23, 95%CI: 1.09, 4.51), however this was not statistically significant in the adjusted model. There were however significant associations detected in the adjusted model for HIV status, insurance type and telemedicine utilization respectively. DISCUSSION/SIGNIFICANCE: This study demonstrates the ongoing need for health services during the recent pandemic and overall willingness of AYA to utilize telemedicine. Given the sexual health disparities faced by AYA, who bear more than half of the 50 million STI cases in the US, optimizing services for AYA is essential and consistent with new laws expanding telehealth use.